Finding Airon Deficiency Anemia (IDA)at Young Women with Overweigth or Obesity - Ayusari, Amelya Augusthina; Azizah, Shofura; Wijayanti, Lilik; Indarto, Dono; Suselo, Yuliana Heri; Mashuri, Yusuf Ari; Hastami, Yunia; Rahayu, Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Background: Young women can suffer from anemia due to monthly menstruation and by having many activities without adequate iron-filled nutrition. Otherproblems found on them are overweight and obesity. The data show that one with overweight or obesity can lead to iron deficiency anemia (IDA) along with increasingproinflammatory cytokines, which will cause the transcription of hepcidin. The increaseof hepcidin transcription will inhibit the absorption of iron from the intestine into the circulation, inhibiting spending iron reserves into circulation, and inhibitingthe release of iron recycled from splenic macrophages. This can cause IDA. The purpose of this study was to obtain the proportion of iron deficiency anemia in overweight or obese young women.Methods: The design of this study was cross sectional using purposive sampling. The subjects of this study were the student from fiveselected Senior high schools inBoyolali, Central Java, Indonesia. The determination of IDAis done by using hemoglobin and indexes of erythrocytes. Results: This study was the follow-upof the previous study, which was conducted to 14 obese and/or overweightyoung women withanemia From 14 subjects, there wasone subject suffered from other anemia and 13 subjects with IDA (using index erythrocytes examination). Their mean of MCV was 72.68±4.29fl, MCH was 23.08±2.63pg, and MCHC was 35.21±0.65 %.Conclusions: From this study, almost all overweight or obeseyoung women with anemia were indicated as IDA (92.8%).